STRATEGI KOMUNIKASI PEMASARAN DALAM MENGHADAPI PERSAINGAN BISNIS DI KOTA MALANG (STUDI KASUS PADA BISNIS PEMAIN DAN PECINTA SEPAK BOLA) - Abdul Hakim (Jurnal Inovasi Penelitian, 2020)
Marketing communication as an important role in dealing with business competition with competitors who have different mindsets. business is not an easy thing for any company to do as well as the business of a football athlete who will also compete with the business of football lovers. Therefore, marketing communication strategy is very necessary to be applied to business people in facing business competition. The purpose of this study to determine the marketing communication strategy in facing of business competition conducted by one of the athlete and lovers of football in the city of Malang. Dist41ct Football Merchandise is a business owned by football athlete, and Oyisam Clothing is a football apparel business in Malang. Based on the results of interviews and observation at the research site, the athlete's business and football lovers were applied five techniques of promotion mix of Philip Kotler's theory of advertising techniques, sales promotion, public relations and publicity, personal sales and direct sales. The application of promotional by football athlete and football fans to face the competition also increases the interest of the buyers and introduces their products to the world.